Profiling of lung microbiota discloses differences in adenocarcinoma and squamous cell carcinoma - Gomes, Sílvia (2019)
We would like to thank all patients for donating their samples and for collaborating in this study. IPATIMUP integrates the i3S Research Unit, which is partially supported by the Portuguese Foundation for Science and Technology (FCT). This work was supported by the Portuguese Foundation for Science and Technology (FCT), financed by the European Social Funds (COMPETE-FEDER) and National Funds through the FCT (projects PEstC/SAU/LA0003/2013 and POCI-01-0145-FEDER-007274, fellowships SFRH/BPD/77646/2011 and SFRH/BPD/120777/2016 to S.G. and P.I.M., respectively, grant PTDC/BEXGMG/0242/2012 to S.S. and by Programa Operacional Regional do Norte (ON. 2 - O Novo Norte and Norte 2020), through FEDER funds under the Quadro de Referencia Estrategico Nacional (QREN; projects NORTE-07-0162-FEDER-00018 and NORTE-070162-FEDER-000067, and NORTE-01-0145-FEDER-000029).